Non-edible palm oil : alternative to mineral based lubricant in metal forming process - Mohd. Ahyan, Nurul Aini (2015)
In this paper, the effect of non-edible oil in cold extrusion process were investigated by cold work forward plane strain extrusion experiments. It then was compared to existing metal forming lubricant additive free paraffinic mineral oil, VG95 and commercial extrusion oil. A pair of taper die and a symmetrical work piece (billet) was placed inside extrusion rig which acted as main experimental apparatus. The experimental result shows that nonedible oil has similar maximum extrusion load with mineral based lubricant and commercial extrusion oil.